On the Femininity of the Swamp. Reading the Monstrous Garden of Fertility, Fermentation, Decay - Chawrilska, Irena; Dolphijn, Rick (Przestrzenie Teorii, 2025)
Swamps are often portrayed as desolate and dangerous places: demonic, inaccessible, marshy, boggy terrains. They have been imagined as an orbis exterior, an untamed space symbolically associated with the boundary between the earthly and otherworldly orders, between life and death: in-between places, not quite land and not quite water. In this article, we explore the swamp from a transdisciplinary and more-than-human perspective. Traversing history, literary studies but also biochemistry and all studies of life, our aim is to practice a holistic approach that does justice to the complexity of swamp, and the many processes (like fertility, fermentation, decay) that give form to its being. Our main finding concerns the femininity ascribed to the swamp and to swamp life (its monstrosities) in the various stories being told. All too often these stories turned around ‘the unaccepted’, and showed how society projects its ideas of ‘unacceptedness’ on swamp life, on right and wrong behavior, and of course on how the female was subjected to patriarchy for so long. It is no coincidence that the unaccepted is time again translated and personified into some form of femininity. Why does the marsh garden so often speak through the body of the woman, her fertility, her sexuality, her feared powers? These gardens, swamps and marshes, were always to be found outside of the city, outside of the civilized land. These analyses show us how geometry is deeply political, sexual and in many ways, enacts and reproduces the ethics of patriarchy.